Hydration Numbers of Carbohydrates in Dilute Aqueous Solutions at Different Temperatures - S. Dhondge, Sudhakar; Dhondge, Alka (Asian Journal of Chemistry, 2012)
Hydration numbers (nh) of glucose, fructose, galactose, sucrose, lactose, a-methyl glucoside and, b-methyl glucoside have been computed at 278.15, 288.15 and 298.15 K by Shiio's method using density and speed of sound data. It has been observed that at 298.15 K hydration numbers of glucose and fructose are of the same order the value which is less for galactose. In the case of disaccharides the value is very high for lactose than sucrose while, a-methyl glucoside seems to be more hydrated than b-methyl glucoside. The behaviour at 278.15 K and 288.15 K was found to be different. Galactose shows very high values as compared to glucose and fructose, whereas, other carbohydrates show the same trends. These results have been interpreted in terms of stereo specificity of carbohydrates in interactions with water as observed in volumetric and compressibility studies.